Chorioamnionitis and neonatal outcome in preterm infants: a clinical overview. (2nd May 2016) - Pugni, Lorenza; Pietrasanta, Carlo; Acaia, Barbara; Merlo, Daniela; Ronchi, Andrea; Ossola, Manuela Wally; Bosari, Silvano; Mosca, Fabio
Abstract: The term chorioamnionitis is used to refer to an intrauterine infection/inflammation occurring between the maternal tissues and the fetal membranes (choriodecidual space) or in the fetal annexes (chorioamniotic membranes, amniotic fluid, umbilical cord). Histological examination of the placenta is the gold standard for diagnosis. However, clinical, biochemical and microbiological criteria are also used to define the disease. The literature contains a large body of evidence showing that chorioamnionitis is the leading cause of very preterm birth and, therefore, contributes significantly to neonatal morbidity and mortality. In recent decades, numerous studies have attempted to establish whether, and to what extent, intrauterine infection/inflammation might negatively affect the short- and long-term outcome of preterm infants. The question is still unanswered. The discrepancy observed across studies can be attributed largely to the use of different inclusion and exclusion criteria, diagnostic criteria and methods, and to whether or not potential confounding factors, such as gestational age were considered. Anyhow, the association between chorioamnionitis and severe prematurity requires serious efforts by researchers to clarify the mechanisms linking intrauterine infection/inflammation with preterm birth, and thus to identify strategies that may guide clinicians' diagnostic and therapeutic choices, with regard to both mothers and infants.